2013
DOI: 10.1007/s12639-013-0307-4
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of a new focus of visceral leishmaniasis due to Leishmania infantum in Golestan Province, north-eastern of Iran

Abstract: Over the last decade, a few cases of visceral leishmaniasis (VL) have been reported in some districts of the province of Golestan, in north-eastern Iran. The aim of the present study was to investigate the prevalence of Leishmania infantum infection among humans and domestic dogs by using direct agglutination test (DAT) and PCR assays in the eastern zone of the province. Between 2011 and 2012, blood samples were randomly collected from 450 humans and 50 domestic dogs, in the eastern zone of Golestan Province i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 23 publications
1
11
2
Order By: Relevance
“…2.8% and 1.3% of human samples were positive by PCRand DAT, respectively. Also, 32% and 30% of dogs were seropositive and PCRpositive, respectively, in these villages (Fakhar et al, ). By the expansion of study in 2016, new infected cases were found in studied areas, where 16% ( n = 131) and 1% ( n = 8) of 800 human samples and ( n = 25) and ( n = 7) of 100 dog samples were positive by PCRand DAT methods, respectively (unpublished data by the same research team).…”
Section: Methodsmentioning
confidence: 96%
See 2 more Smart Citations
“…2.8% and 1.3% of human samples were positive by PCRand DAT, respectively. Also, 32% and 30% of dogs were seropositive and PCRpositive, respectively, in these villages (Fakhar et al, ). By the expansion of study in 2016, new infected cases were found in studied areas, where 16% ( n = 131) and 1% ( n = 8) of 800 human samples and ( n = 25) and ( n = 7) of 100 dog samples were positive by PCRand DAT methods, respectively (unpublished data by the same research team).…”
Section: Methodsmentioning
confidence: 96%
“…According to the increasing number of viscerotropic cases, L. tropica , the most important aetiological agent of anthroponotic CL (ACL), has been recently known as the second aetiological agent of VL in this country (Ghatee, Mirhendi, et al, ). Also, new emerging foci of ZVL have been found in western and north‐eastern parts of the country (Fakhar et al, ; Hamzavi et al, ). Northern regions of Iran in the southern coast of Caspian Sea and with condensed forests and humid weather consisted of three provinces Guilan, Mazandaran and Golestan that have been non‐endemic areas for ZVL.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on canine leishmaniosis from Turkey, Iran and Saudi Arabia have reported between 1.6% and 42% positivity for Leishmania spp. by PCR of dogs surveyed using blood or other tissue samples [ 27 29 ]. The detection of positive kDNA PCR in 22.7% of the dogs in the current study from central Israel is therefore compatible with the infection rates found in other Middle Eastern countries.…”
Section: Discussionmentioning
confidence: 99%
“…For VL due to L. ( L. ) infantum and L. ( L. ) donovani , this test can be easily performed using serum or urine samples of patients [ 163 ]. This method showed high sensitivity (74.6–96.6%) and specificity (77.8–100%) in patients from Brazil, Spain, Kenya, Sudan, Ethiopia, and Nepal [ 50 , 71 , 86 , 87 , 90 , 91 ]. This test is also useful as marker of asymptomatic infection and in HIV co-infected individuals, showing sensitivity and specificity values of 81–91.3% and 83.3–90%, respectively [ 86 , 164 , 174 , 175 ].…”
Section: Immunological Methods For Diagnosis Of Leishmaniasismentioning
confidence: 99%